Bulbophyllum jingdongense (Orchidaceae), a new species in the Cirrhopetalum alliance from South China and Laos - Hu, Ai-Qun; Ye, De-Ping; Gale, Stephan W.; Saunders, Richard M. K.; Fischer, Gunter A.; Li, Jian-Wu (Phytotaxa, 2017)
Bulbophyllum jingdongense, a new species from South China and Laos belonging to the Cirrhopetalum alliance (Orchidaceae), is described and illustrated. It is morphologically distinct from all other known species in the alliance on account of the following diagnostic characters: pseudobulbs compressed subglobose; sepals and petals with dense, reddish-purple papillae on abaxial surfaces; lateral sepals basally connivent along their lower edges, the upper edges strongly incurved and connivent at the middle and then becoming separate again towards their incurved, horn-shaped, obtuse apex; column with a single orange-yellow gland below the stigma; and stelidia well-developed, 2.5–3 mm long, truncate at base, acuminate, merging with the column wings on each side of the column. The conservation status of B. jingdongense is assessed and taxonomic notes are provided.